Br...O contacts and π–π stacking dominate the packing in methyl 4‐bromo‐3, 5‐dimethoxybenzoate. (18th June 2013) - Saeed, Aamer; Qasim, Muhammad; Simpson, Jim
Abstract : The title compound, C10 H11 BrO4, a useful precursor to pharmaceutically active isocoumarin and isochroman derivatives, crystallizes with two unique molecules in the asymmetric unit. A π–π stacking interaction links the planar molecules in the asymmetric unit. Additional π–π contacts stack pairs of molecules along the c axis. A feature of the crystal packing is the presence of a number of short Br...O contacts. A particularly unusual arrangement involves the formation of dimers, with pairs of Br...O contacts imposing a close Br...Br interaction and generating five‐membered rings within an eight‐membered ring formed by two Br...O contacts. Only two comparable arrangements have been reported previously. The Br...O contacts combine with weak C—H...O hydrogen bonds to form corrugated sheets of molecules approximately parallel to (001). These sheets are stacked along the c axis by π–π interactions to generate a three‐dimensional network.